THE SIGNIFICANCE OF PHYSICAL EXERCISES IN THE DEVELOPMENT OF EDUCATION, HEALTH AND PROFESSIONAL SKILLS OF YOUNG STUDENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article describes the importance of physical exercises in the education of young students, health and educational activities in sports clubs, the proper organization of physical education classes and sports clubs.